TELEODONTOLOGY AND ORAL HEALTH: CHALLENGES AND PERSPECTIVES - Monteiro de Moraes, Isabella; Alves Vieira, Plínio; De Borborema Garcia Pedreira, Juliana; Nelo Pedreira, Erick (Health and Society, 2022)
The association between internet, information and communication technologies and their interaction with health areas, especially dentistry, corroborated the advent of Teledentistry; this, in turn, is subdivided into two main axes: Tele-education and Tele-assistance, the last being related to dental care, providing a second opinion. Teledentistry comprises “distance care and/or teaching”, which represents professionals in the field of dentistry such as Dental Surgeons (CD) using technological tools that enable the diagnosis, monitoring and treatment of the patient, in addition to promote training and knowledge exchange among professionals in the dental field. The aim of this study is to discuss the challenges and perspectives related to Teledentistry. This study was conducted through bibliographic surveys extracted from the electronic databases PUBMED/MEDLINE and BIREME. From the study and discussion of such articles, it was concluded that Teledentistry is an area in great development of an essential character in the dissemination of scientific knowledge in the health sciences.